Pituitary Hormones and Orofacial Pain - Dussor, Gregory; Boyd, Jacob T.; Akopian, Armen N. (Frontiers in Integrative Neuroscience, 2018)
Clinical and basic research on regulation of pituitary hormones, extra-pituitary release of these hormones, distribution of their receptors and cell signaling pathways recruited upon receptor binding suggests that pituitary hormones can regulate mechanisms of nociceptive transmission in multiple orofacial pain conditions. Moreover, many pituitary hormones either regulate glands that produce gonadal hormones (GnH) or are regulated by GnH. This implies that pituitary hormones may be involved in sex-dependent mechanisms of orofacial pain and could help explain why certain orofacial pain conditions are more prevalent in women than men. Overall, regulation of nociception by pituitary hormones is a relatively new and emerging area of pain research. The aims of this review are to (1) present an overview of clinical conditions leading to orofacial pain that are associated with alterations of serum pituitary hormone levels; (2) discuss proposed mechanisms of how pituitary hormones could regulate nociceptive transmission; and (3) outline how pituitary hormones could regulate nociception in a sex-specific fashion. Pituitary hormones are routinely used for hormonal replacement therapy, while both receptor antagonists and agonists are used to manage certain pathological conditions related to hormonal imbalance. Administration of these hormones may also have a place in the treatment of pain, including orofacial pain. Hence, understanding the involvement of pituitary hormones in orofacial pain, especially sex-dependent aspects of such pain, is essential to both optimize current therapies as well as provide novel and sex-specific pharmacology for a diversity of associated conditions.